PERKEMBANGAN KEPRIBADIAN MANUSIA SEBAGAI PROSES PENGENALAN DIRI YANG SEJATI = (The Development of Man's Personality as a Process of the Real Self Knowledge) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The aims of this research is to formulate Jung's philosophycal understanding about the development of man's personality as a process of the real self-knowledge. This research is based on the works of Carl Gustav Jung, and other literatures which are related to the main study of this research. Theoretical description, interpretation, coherence, and reflection were used in the analysis of the collected data. The result of this research clarifies the development of man's personality as a process of the real self knowledge. This means that the development of man's personality is not mechanical but a concious ethical decision making process. Achievement of self-actualization involves ability to learn and to overcome conflicts as well as knowledge about the psychological resources in his self. Keywords: Man's personality -- self â knowledge